Pemberdayaan Usaha Mikro Emping Melinjo di Padukuhan Koteng dengan Optimalisasi Produk guna Meningkatkan Harga Jual - Nurul Dzakiya; Desi Kiswiranti; Subhan Arif; Radhitya Adzan Hidayah; Hidayat (UNIB Press, 2024)
Optimizing emping products has an important role in increasing sales value for micro businesses. Emping, as one of Indonesia's traditional foods, has great potential in the local and international market. However, to gain a competitive advantage, micro businesses need to pay attention to the quality of emping products as a whole, from raw materials to the production process. This service explores strategies for optimizing emping products with a focus on improving quality, production efficiency and appropriate marketing in emping melinjo micro businesses in Padukuhan Koteng, Kapanewon Mlati, Sleman. The method used includes presenting material about the importance of understanding the optimization of emping products in increasing their selling value. By taking the right steps to improve quality and production efficiency, as well as implementing effective marketing strategies, micro businesses can optimize the potential of their emping products and achieve success in an increasingly competitive market. The results of the service show that efforts to optimize emping products require improvements in various aspects, such as selecting quality raw materials, using efficient production technology and targeting marketing strategies. By implementing this strategy, micro businesses can increase the selling value of emping products, expand market share, and achieve better business sustainability.